Preclinical assessment of the neutralizing capacity of antivenoms produced in six Latin American countries against medically-relevant Bothrops snake venoms - Segura Ruiz, Álvaro (2010)
Species of the genus Bothrops induce the vast majority of snakebite envenomings in Latin America. A preclinical study was performed in the context of a regional network of public laboratories involved in the production, quality control and development of antivenoms in Latin America. The ability of seven polyspecific antivenoms, produced in Argentina, Brazil, Peru, Bolivia, Colombia and Costa Rica, to neutralize lethal, hemorrhagic, coagulant, defibrinogenating and myotoxic activities of the venoms of Bothrops neuwiedi (diporus) (Argentina), Bothrops jararaca (Brazil), B. neuwiedi (mattogrossensis) (Bolivia), Bothrops atrox (Peru and Colombia) and Bothrops asper (Costa Rica) was assessed using standard laboratory tests. Despite differences in the venom mixtures used in the immunization of animals for the production of these antivenoms, a pattern of extensive cross-neutralization was observed between these antivenoms and all the venoms tested, with quantitative differences in the values of effective doses. This study reveals the capacity of these antivenoms to neutralize, in preclinical tests, homologous and heterologous Bothrops venoms in Central and South America, and also highlight quantitative differences in the values of Median Effective Doses (ED50s) between the various antivenoms.